Bridge to Healing: A Comprehensive Review of the Oroantral Fistula Journey - Savitha Lakshmi Raghavan; Jayasrikrupaa Ravi; Suganya P; Ramya Chandrasekaran; Ramu Shobhana (Oral Sphere Journal of Dental and Health Sciences, 2025)
Oroantral fistula (OAF) is a pathological condition characterized by an abnormal communication between the oral cavity and the maxillary sinus. This communication leads to a persistent opening between these two anatomical regions, allowing the passage of oral fluids, food particles and microbial flora into the maxillary sinus. OAF can result from various causes including failed primary healing following dental extractions particularly in the posterior maxillary region, trauma, chronic dental infections, osteomyelitis, radiation therapy and iatrogenic complications during surgical procedures involving the maxilla. The clinical presentation of OAF often includes symptoms such as persistent or recurrent sinus infections, nasal discharge, foul taste or smell and sometimes even oro-nasal regurgitation of liquids. Diagnosis is typically confirmed through clinical examination and imaging studies such as dental radiographs or computed tomography (CT) scans, which help to visualize the fistulous tract and assess its size and extent. Management of OAF aims to close the fistulous tract and restore the integrity of the oral and sinus cavities. Treatment options vary depending on the size, location and underlying cause of the fistula. Conservative measures may include observation, nasal decongestants and antibiotics to control infection. However, surgical intervention is often necessary for definitive closure of the fistula. Surgical techniques range from simple primary closure with local flaps to more complex procedures involving bone grafts or soft tissue flaps depending on the size and complexity of the defect. This comprehensive review comprehensively explores the etiology, clinical manifestations, diagnostic modalities and management strategies pertaining to oroantral fistula (OAF).